Meningkatkan Kepuasan Kerja dan Kinerja Perusahaan dengan Telecommuting - Ardhanari, Margaretha (Jurnal Widya Manajemen & Akuntansi, 2001)
Working Condition today is rather complicated and it influences the job satisfaction of workers and the performance of companies. On one side, the employers want the employees to work more productively and on the other, the employees want the employers to be more flexible. At the same time, the employees' awareness of being much closer to their family is demanding. There is a belief that if employees feel good about their personal life and it is supported by the working conditions in the work place, then they will do their best to get their work done well without any burden. This atmosphere will create a job satisfaction and simultaneously will influence the performance of the companies. The flexible work patterns are an obvious response to employees' call for more work/life balance. Based in prior research it is believed that telecommuting, the one of flexible work pattern has proven to be win-win situation. Telecommuting is the practice of working at home or at satelite location near the home where employees use computers and telecommunication technology in lieu of physically traveling to a central work place. The objective of this article is to study telecommuting as an alternative work pattern in order to increase the job satisfaction of employees and the performance of the organization.